A bridge across the ocean - Meissner, Susan, 1961- (Berkley, 2017)
"World War Two is over, but the recovery from the most intimate of its horrors has only just begun for Annaliese Lange, a German ballerina desperate to escape her past, and Simone Deveraux, the wronged daughter of a French Resistance spy. Now the two women are joining hundreds of other European war brides aboard the renowned RMS Queen Mary to cross the Atlantic and be reunited with their American husbands. Their new lives in the United States brightly beckon until their tightly-held secrets are laid bare in their shared stateroom. When the voyage ends at New York Harbor, only one of them will disembark ... Present day. Facing a crossroads in her own life, Brette Caslake visits the famously haunted Queen Mary at the request of an old friend. What she finds will set her on a course to solve a seventy-year-old tragedy that will draw her into the heartaches and triumphs of the courageous war brides--and will ultimately lead her to reconsider what she has to sacrifice to achieve her own deepest longings."--